Man on the moon - Suen, Anastasia; Huang, Benrei (New York : Viking, 1997)
Describes in illustrations and simple text the Apollo 11 mission to the moon, culminating in man's first lunar landing.
Adult 230
Accelerated Reader AR
Keywords: Project Apollo (U.S.) -- Juvenile literature; Apollo 11 (Spacecraft) -- Juvenile literature; Project Apollo (U.S.); Apollo 11 (Spacecraft); Space flight to the moon -- Juvenile literature; Space flight to the moon